Late Cretaceous Ostracoda in the Shiranish Formation Dokan Area, Kurdistan Region-NE Iraq - Taha, Zardasht Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2020)
Ostracods are described for the first time from Late Cretaceous (Late Campanian - Maastrichtian) deep marine sediments of the Shiranish Formation of Dokan area. They were collected using a new technique for releasing ostracod shells from a bluish white marl and marly limeston (hemipelagite). Twenty- two ostracod species are identified, belonging to the genera Bythocypris, Cytherella, Cypridopsis, Eucypris, Krithe, Mongolianella, Paracypris, Paracypretta, Parakrithe and Xestoleberis. Only eight ostarcods species belonging to ten genera are systematically described as detail. The ostracod fauna supports a Late Cretaceous (Late Campanian- Early Maastrichtia) age for the Shiranish Formation of Dokan area.
Keywords: Ostracods; Late Cretaceous (Late Campanian- Early Maastrichian); Shiranish Formation; Dokan area; Kurdistan region; Northeastern Iraq